Vascular Function, Cerebral Cortical Thickness, and Cognitive Performance in Middle‐Aged Hispanic and Non‐Hispanic Caucasian Adults. Issue 4 (26th February 2015) - Pasha, Evan P.; Kaur, Sonya S.; Gonzales, Mitzi M.; Machin, Daniel R.; Kasischke, Kennon; Tanaka, Hirofumi; Haley, Andreana P.
<x xml:space="preserve">Abstract</x> Hispanics are at increased risk for acquiring cardiovascular risk factors that contribute to cognitive dysfunction. To compare indices of vascular health with measures of cerebral gray matter integrity, 60 middle‐aged Hispanic and non‐Hispanic Caucasian participants were matched across age, sex, years of education, and mental status. Arterial stiffness was characterized by β‐stiffness index and carotid‐femoral pulse wave velocity, and magnetic resonance imaging estimated cortical thickness in a priori regions of interest known to be susceptible to vascular risk factors. Measures of arterial stiffness were significantly higher in Hispanics than in non‐Hispanic Caucasians. Hispanics exhibited thinner left inferior frontal gyrus (LIFG) cortical thickness (P=.04) with concurrently lower language (P=.02), memory (P=.03), and attention‐executive functioning (P=.02). These results suggest that compromised vascular health may occur simultaneously with cortical thinning of the LIFG as an early neuropathological alteration in Hispanics.